2005
DOI: 10.1242/dev.01916
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans sperm bud vesicles to deliver a meiotic maturation signal to distant oocytes

Abstract: The major sperm protein (MSP) is the central cytoskeletal element required for actin-independent motility of nematode spermatozoa. MSP has a dual role in Caenorhabditis elegans reproduction, functioning as a hormone for both oocyte meiotic maturation and ovarian muscle contraction. The identification of the signaling function of MSP raised the question, how do spermatozoa, which are devoid of ribosomes, ER and Golgi, release a cytoplasmic protein lacking a signal sequence? Here, we provide evidence that MSP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 42 publications
5
136
2
Order By: Relevance
“…The following antibodies were used for Western blot analysis: rabbit anti-GSP-3/4 [the epitope used for antibody generation (Chu et al 2006) is shown in blue text in Figure S1C] at 1:4000, mouse anti-MSP (Greenstein laboratory) at 1:1000 dilution (Kosinski et al 2005), mouse anti-a-tubulin (clone B-5-1-2; Sigma, St. Louis) at 1:500 dilution, and HRP-conjugated goat anti-rabbit at a 1:5000 dilution. HRP signal was detected using SuperSignal Chemiluminescent Substrate (Pierce Chemical, Rockford, IL).…”
Section: Analysis Of Gsp-3/4 Protein Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following antibodies were used for Western blot analysis: rabbit anti-GSP-3/4 [the epitope used for antibody generation (Chu et al 2006) is shown in blue text in Figure S1C] at 1:4000, mouse anti-MSP (Greenstein laboratory) at 1:1000 dilution (Kosinski et al 2005), mouse anti-a-tubulin (clone B-5-1-2; Sigma, St. Louis) at 1:500 dilution, and HRP-conjugated goat anti-rabbit at a 1:5000 dilution. HRP signal was detected using SuperSignal Chemiluminescent Substrate (Pierce Chemical, Rockford, IL).…”
Section: Analysis Of Gsp-3/4 Protein Levelsmentioning
confidence: 99%
“…The following primary antibodies were used: rat anti-GSP-3/4 (rt1494) at 1:50 and rat anti-GSP-3/4 (rt1495) at 1:25; rabbit anti-GSP-3/4 (rb1496) at 1:2000 and rabbit anti-GSP-3/4 (rb1497) at 1:1000 (Chu et al 2006); monoclonal antibody 1CB4 at 1:500 or a AlexaFluor 488-conjugated wheat-germ agglutinin at 5 mg/ml [W11261 from Invitrogen (Carlsbad, CA)], which recognizes membranous organelles (MO) in sperm Okamoto and Thomson 1985;Kelleher et al 2000); and mouse anti-MSP 4A5 antibody from the Developmental Studies Hybridoma Bank at 1:5 or the Greenstein laboratory at 1:50 (Kosinski et al 2005). Secondary antibodies include anti-rabbit AlexaFluor 488-labeled IgG, anti-rat AlexaFluor 488-labeled IgG, and anti-rabbit AlexaFluor 546-labeled IgG at 1:100.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The -2 oocyte then moves into the -1 position where it will undergo maturation/ovulation $23 min later. In hermaphrodites with sperm, the signal that triggers maturation/ovulation is constitutive: the major sperm protein (MSP) secreted from sperm (McCarter et al 1999;Miller et al 2001;Kosinski et al 2005). By contrast, in animals without sperm (sex determination mutant females, adult hermaphrodites that have exhausted their self-sperm), oocytes form but are arrested in diakinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Bivalents are then connected only by crossovers and sister-chromatid cohesion (Schvarzstein et al 2010). Late diakinesis nuclei cellularize to form oocytes and remain arrested with six bivalents until ovulation is triggered by sperm (Miller et al 2001;Kosinski et al 2005).The germline of kin-18 mutants was smaller with reduced numbers of nuclei per zone compared to wild type ( Figure 1I and Table S1). Without having a marker for meiotic progression that can differentiate all of the meiotic stages it is difficult to assess which nuclei are at any particular meiotic stage in kin-18 mutants.…”
mentioning
confidence: 99%
“…Then a signal from sperm, mediated by the major sperm protein, triggers the activation of MPK-1 in the proximal diakinesis oocyte. This activation leads to exit from meiotic prophase I and to the initiation of ovulation and the meiotic divisions (Miller et al 2001;Kosinski et al 2005). Thousand And One (TAO) kinases were originally identified as mammalian homologs of Ste20 protein kinase in Saccharomyces cerevisiae (Hutchison et al 1998;Chen et al 1999).…”
mentioning
confidence: 99%